MAIA, Marcus. (Org.). Psicolinguística e Educação. São Paulo: Mercado de Letras, 2018, 258 p. - Da Silva Cabral, Marina; De Azevedo, Bruno (Revista da Anpoll, 2020)
Resenha do livro Psicolinguística e Educação, organizado por Marcus Maia.